Novel GLP-1 analog supaglutide improves glucose homeostasis in diabetic monkeys. Issue 2 (February 2021) - Cui, Qiaoli; Liao, Yijing; Jiang, Yaojing; Huang, Xiaohang; Tao, Weihong; Zhou, Quanquan; Shao, Anna; Zhao, Ying; Li, Jia; Ma, Anran; Wang, Zhihong; Zhang, Li; et al.
Abstract : Glucagon-like peptide 1 (GLP-1) is an insulinotropic hormone and plays an important role in regulating glucose homeostasis. GLP-1 has a short half-life (t1/2 < 2 min) due to degrading enzyme dipeptidyl peptidase-IV and rapid kidney clearance, which limits its clinical application as a therapeutic reagent. We demonstrated recently that supaglutide, a novel GLP-1 mimetic generated by recombinant fusion protein techniques, exerted hypoglycemic and β-cell trophic effects in type 2 diabetes db/db mice. In the present study, we examined supaglutide's therapeutic efficacy and pharmacokinetics in diabetic rhesus monkeys. We found that a single subcutaneous injection of supaglutide of tested doses transiently and significantly reduced blood glucose levels in a dose-dependent fashion in the diabetic monkeys. During a 4-week intervention period, treatment of supaglutide of weekly dosing dose-dependently decreased fasting and random blood glucose levels. This was associated with significantly declined plasma fructosamine levels. The repeated administration of supaglutide remarkably also decreased body weight in a dose-dependent fashion accompanied by decreased food intake. Intravenous glucose tolerance test results showed that supaglutide improved glucose tolerance. The intervention also showed enhanced glucose-stimulated insulin secretion and improved lipid profile in diabetic rhesus monkeys. These results reveal that supaglutide exerts beneficial effects in regulating blood glucose and lipid homeostasis in diabetic rhesus monkeys.